Communication by image (Journal of Parents and Teachers, 1996)
It uses an informal and persuasive style, with an explanatory and commercial tone. It is characterized by being familiar and insinuating, seeking to connect with the audience in an effective way. It also incorporates humorous elements to maintain interest.
Keywords: Cinema and education; cross curricular films